A hydraulic-pump speed controller in agricultural sprayers based on the automation and use of the control area network (CAN) bus - Galdino Ferreira, Carlos A. J.; Cruvinel, Paulo E.; Penaloza, Elmer A. G. [UNESP]; Oliveira, Vilma Alves [UNESP]; Mercaldi, Heitor V. [UNESP]; IEEE (Ieee Computer Soc, 2018)
This paper presents the development of a speed control for a hydraulic pump based on automation and the use of the controller area network (CAN bus). As components of the project its result are considering the analysis of the level of automation achieved, the flow measurements, both the pressure and drive current of the spray pump used, including the various forms of combining the nozzles for the spray application. In order to understand how the automatization for speed control occurs, it is necessary to consider the use a computational language, i.e., it is necessary to know the architecture of the control system so that the algorithms can be generated and interpreted properly. Therefore, the structural knowledge of the computational semantics involved in these processes is that it allows the generation of the language codes based on the use of the involved microprocessor. It is important to mention that the interpretation of language is based on mechanisms that search to understand phrases, trying to translate them into a representation that can be understood and used by a microprocessor. The opposite occurs in the language's generation, since a microprocessor system translates a representation for its expression in some language. In this research it was used both the C ++ language and the language for the development of the PIC's algorithms, which leaded to the generation of texts as close as possible to the texts produced by the people. Furthermore, the developed application has required both interpretation and language generation to allow the adequate operation of the speed controller system, i.e., to guarantee the spray quality of pesticides for pest control.
Keywords: semantic computer in agriculture; automation; quality of agricultural application; CAN bus; precision agriculture; sprayer; motor pump speed